PEDAGOGICAL PROFILING IN BELARUSIAN SCHOOLS: SOCIOCULTURAL AND EDUCATIONAL EFFECTS (EDUCATION IN THE 21ST CENTURY, 2023)
Today, when education in all ages and fields is becoming a long-term and promising trend, the role of the teacher as a professional with knowledge, skills and experience in organizing educational activities is being updated. At the same time, society and the educational system are experiencing the consequences of a rather long crisis in the field of teacher training, associated with a sharp decline in the prestige of the teaching profession in the last two decades. As a result - shortages of pedagogical specialties in universities, weak applicants and students. In the Republic of Belarus, over the past five years, this contradiction has been successfully overcome with the help of pedagogical profiling of the educational process at school, which allows identifying and attracting internally motivated and well-performing students to pedagogical specialties in universities.
Keywords: Keywords: profiling, pedagogical profiling, pedagogical classes, continuous pedagogical education.